(1123) hospital layout as a quadratic assignment problem تصميم المستشفى كمسألة تخصيص تربيعية - elshafei, alwalid N. (the institute of national planning, 2018)
the problem of locating hospital departments so as to minimize the total distance travelled by patients could be formulated as a quadratic assignment problem, in this paper we discuss some practical considerations of the problem.